INCLUSIVE DIGNITY AND LAND REFORM IN SOUTH AFRICA - Koopman, Nico (Scriptura, 2014)
This article explores the light that the notion of inclusive dignity might shed on the quest for land reform and land restitution in South Africa. It offers a discussion of the notion of inclusivity by outlining the various faces of exclusivity in contemporary societies, especially on the continent of Africa. It discusses the indispensable role of three dimensions of human rights to acknowledge, affirm and actualize dignity for all, including nature. It argues that dignity can be actualized in two ways, namely through the provision of opportunities for people whose land had been take away, to build a life where the features of dignity are actualized. This implies access to the most basic necessities and goods of life, participation in the political and economic processes of society, and opportunities to develop God-given potentialities. A second mode of actualizing dignity in the context of land restitution processes is that people who choose to return to the original or an equivalent piece of land, be granted the opportunity to return, and that they receive appropriate support from government and other institutions to use the land optimally.